Improving Health Care Linkages for Criminal Justice-Involved Persons: The Cook County Jail Medicaid Enrollment Initiative. (July 2016) - Riedel, Lauren E.; Barry, Colleen L.; McGinty, Emma E.; Bandara, Sachini N.; Webster, Daniel W.; Toone, Robert E.; Huskamp, Haiden A.
The Affordable Care Act has created an unprecedented opportunity to enroll criminal justice-involved individuals in Medicaid. Many jurisdictions within Medicaid expansion states are launching efforts to enroll this population in health insurance and provide connections to services in the community. This study examined one early initiative to enroll individuals in Medicaid during the intake process at the Cook County Jail in Illinois. Several elements were identified as critical to the program's success: key early planning decisions made within the context of a cross-agency group, a high level of dedication among partnering organization leaders, program buy-in among security personnel, and the unique way in which Cook County verifies inmate identity for Medicaid enrollment purposes. These features can potentially guide other jurisdictions attempting to implement similar initiatives.